1998
DOI: 10.1111/j.1440-1827.1998.tb03843.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant hidradenocarcinoma: A report of malignant transformation from nodular hidradenoma

Abstract: A giant hidradenocarcinoma presented by a 75-year-old female is reported. The patient had a malignant transformation within a nodular hidradenoma involving the right postauricular area, which was treated by mass removal and a right radical neck dissection with a free-flap covering. Malignant hidradenocarcinoma is the least common adnexal tumor of uncertain origin. They are usually malignant from their inception, but some develop from a benign counterpart. To the authors' knowledge, only three cases have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 17 publications
0
60
0
Order By: Relevance
“…[1] In our case also the history was very long and likelihood of earlier benign tumor was very high.The size can be very big and this also indicates the aggressiveness of the tumor. [2] These can present with some complication like acute cardiac failure. [3] These tumors require differentiation from metastatic and other malignancies like squamous cell and basal cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In our case also the history was very long and likelihood of earlier benign tumor was very high.The size can be very big and this also indicates the aggressiveness of the tumor. [2] These can present with some complication like acute cardiac failure. [3] These tumors require differentiation from metastatic and other malignancies like squamous cell and basal cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients were disease-freeat27and35months,respectively,and1patient died of metastatic disease. Similarly, Lim et al [9] reported a case of giant hidradenocarcinoma with metastases soon after surgery and adjuvant radiotherapy. Local radiotherapy maybeusefulinthepresenceofdermallymphaticinvasion, nerve-s heathinvolvement,deepstructureinfiltration,positive resection margins, highly anaplastic morphology, and extracapsularlymphnodeextension [8].Furthertrialsareneeded todefinetheroleofradiotherapyandchemotherapy.Estrogenreceptoranalysishasbeenrecommendedbysome authors [5,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…They generally enlarge slowly, can be solid or cystic clinically. When they reach to large sizes they are referred as giant hidradenomas which may present with tenderness and change in skin color (5)(6)(7)(8). Hidradenomas are usually slow growing tumors but as in our case they may show abrupt progression.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis must include cyctic hygroma, soft tissue tumors like fibrosarcoma, synovial cell sarcoma, osteochondroma and neuroblastoma metastasis in childhood (3,9). Histapathology and immunohistochemical staining are helpful in differentiation and final diagnosis (3,8,9). Hidradenomas are characterized by cuboidal or columnar cells lining tubular lumina and they also contain cystic spaces.…”
Section: Discussionmentioning
confidence: 99%